2007
DOI: 10.3113/fai.2007.0162
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Gait Analysis in Patients with First Metatarsophalangeal Joint Arthrodesis for Hallux Rigidus

Abstract: First MTP joint arthrodesis produces objective improvement in propulsive power, weightbearing function of the foot, and stability during gait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 22 publications
3
48
0
2
Order By: Relevance
“…Arthrodesis of the first metatarsophalangeal joint is considered to be the gold-standard technique for treating patients with severe hallux valgus, recurrent hallux valgus and deformities secondary to inflammatory arthritis of the hallux (4)(5)(6)(7)(8)(9)(10)20,21) . In a prospective study, Brodsky et al (6) showed that arthrodesis of this joint improved the stability and propulsive force during gait, for feet with severe joint degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthrodesis of the first metatarsophalangeal joint is considered to be the gold-standard technique for treating patients with severe hallux valgus, recurrent hallux valgus and deformities secondary to inflammatory arthritis of the hallux (4)(5)(6)(7)(8)(9)(10)20,21) . In a prospective study, Brodsky et al (6) showed that arthrodesis of this joint improved the stability and propulsive force during gait, for feet with severe joint degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which the deformity is considered to be moderate or severe, a proximal approach to the first metatarsal is recommended, with the aim of correcting the varus deformity of this bone. Arthrodesis of the first metatarsophalangeal joint is a treatment option for patients with severe hallux valgus, recurrent hallux valgus and deformities secondary to inflammatory arthritis of the first metatarsophalangeal joint, such as in cases of rheumatoid arthritis (4)(5)(6)(7)(8)(9)(10) . Since arthrodesis does not directly address varus deformity of the first metatarsal, there are doubts in relation to patients with an increased intermetatarsal angle regarding whether the varus deformity can be corrected by means of arthrodesis of the first metatarsophalangeal joint alone, or whether osteotomy at the base of the first metatarsal is necessary (11,12) .…”
Section: Introductionmentioning
confidence: 99%
“…However, the same study also showed a statistically significant reduction in ankle torque and ankle power at push-off and a shorter step length and loss of ankle plantar flexion at toe-off. Similarly, Brodsky, et al, 3 compared pre and post operative arthrodesis data and found three statistically significant changes in gait: an increased single limb support time, a decrease in step length but an increase in maximum ankle push off power in contrast to the previous study. Although these finding were attributed to improvements in pain and mechanical stability, mechanics of the 1 st MTPJ were not measured.…”
mentioning
confidence: 92%
“…The technique is advocated for the alleviation of pain and deformity and restoration of the stability and weight bearing function of the first ray by stabilizing the medial column of the foot. 3,10 This technique has been shown to be successful both in pain relief and also in clinical and radiographic evaluation. 9 Despite the high patient satisfaction in terms of pain relief, 1 st MTPJ arthrodesis has been shown to reduce functional gait parameters compared to the contralateral limb.…”
mentioning
confidence: 99%
“…8,17,19,21,22,25 The development of this technology has allowed us to evaluate several foot and ankle conditions and also compare treatments and postoperative outcomes. 4,5,7,16,31 One limitation of current foot and ankle gait analysis models is their inability to uncouple talocrural and subtalar joint motion. These models use skin mounted markers attached to palpable bony landmarks to define the lower leg as one segment and the hindfoot as the adjacent segment.…”
Section: Introductionmentioning
confidence: 99%